Titanium Reconstruction Nailing For Sub - Trochanteric Fractures of Femur - Ashish Kumar Jose; Surendher Kumar R.; Krishnagopal R; Sandeep MMR (International Journal of Medical Research and Review, 2015)
Introduction: Sub-trochanteric fractures of femur present a challenging situation to the orthopaedic surgeons world-wide. Complications like malunion, nonunion and implant failure are high. Several implants have been designed for fixation of sub-trochanteric fractures. In this study we analyze the functional and radiological outcome of sub-trochanteric fractures treated by Titanium Reconstruction nails.Methods: This is a prospective study. 20 patients with sub-trochanteric fractures treated by Titanium reconstruction nail from June 2012 to December 2014 were included in the study. We analyzed these 20 patients for functional and radiological outcome and complications.Results: The fracture union rate was 100 % and the average union time was 14 weeks. 3 patients had varus malunion and shortening was noted in 4 patients. 85% of the patients had excellent to good functional outcome.Conclusion: We concluded that Titanium Reconstruction nail is an ideal implant for sub-trochanteric fractures with an excellent union rate and a very good functional outcome.